"We're giving them the tools." A qualitative study of nursing students working with Recovery College trainers to support student wellbeing. Issue 1 (28th August 2021) - Oates, Jennifer; Hassan, Rasiha; Coster, Sam
Abstract : Purpose: This paper aims to present a thematic analysis of student nurses' experiences of an innovative collaboration between a mental health Recovery College and a nursing faculty, where Recovery College trainers' expertise in co-production and peer facilitation were foregrounded. The aim of this study is to understand how nursing students experienced being peer facilitators of well-being workshops for fellow students following training with Recovery College trainers. Design/methodology/approach: Thematic analysis of qualitative data from eight semi-structured interviews and a focus group with 15 participants. Findings: The overarching theme that emerged was "The process of being a student Peer Facilitator". Six themes emerged from the data: "What we brought"; "Conceptualisation"; "Adaptation"; "we're giving them the tools"; "What we gained"; and "Development". Practical implications: Mental health nurse educators could forge collaborative relationships with Recovery College colleagues with a broader remit than service users' "lived experience" of mental distress. Student nurses should be given opportunities to be peer facilitators and draw on their lived experience as student nurses as means of addressing their and their peers' mental health. Originality/value: Original findings were that the student experience of being a peer facilitator was different to their other experiences in education and clinical practice. They drew on their lived experience throughout and found that they learned skills to address their well-being through supporting other students to improve theirs.